Competitiveness of selected South-Eastern European countries in European Union wood flooring market : Konkurentnost odabranih zemalja jugoistočne Europe na tržištu drvenih podova Europske unije - Glavonjić, Branko (Array, 2020)
Selected South-Eastern European countries (SEEC - Albania, Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, Serbia and Slovenia) represent significant producers and exporters of wood flooring in Europe. In 2018, 9.4 % of Europe’s wood flooring production originated from this region. The region is a net exporter of wood flooring since it exports over 50 % of total production. The most important market for the export of wood flooring is the European Union with a share of over 60 % in total exports. Trends in this market are important for manufacturers and exporters from the region. Therefore, the analysis of the impact of the European Union imports on wood flooring production in the SEEC was conducted by application of econometric modelling. The parameters of the obtained model show that the increase of approximately 0.75 % could be expected in the production of wood flooring in selected South-Eastern European countries for each precentral increase in the European Union imports. In addition to these results, the paper presents the analysis of the competitiveness of wood flooring export from the region measured by the Competitiveness Growth Index (RCA1). The aim of this analysis was to quantify the level of their price and non-price competitiveness in the European Union market. Conducted analyses show that the Competitiveness Growth Index (RCA1) had positive values (higher than one) for most significant countries from the SEEC for most of the observed period.